Comparing Live and Virtual Simulation for Multi-Agency UAS Operations - Hammar Wijkmark, Cecilia; Heldal, Ilona; van Laere, Joeri (Proceedings of the International ISCRAM Conference, 2026)
As emergency response organizations implement Unmanned Aerial Systems (UAS), the complexity of multi-agency incident scenes increases, requiring targeted training for incident commanders. This study compares two exercise formats: Live Simulation (LS) and Virtual Simulation (VS), using five predefined UAS coordination events to examine their distinctive values and inform exercise design. Data were collected from 30 subjects over 2 days in both formats using a multiple-case study design. VS offered superior controllability and cue salience for complex scenarios, while LS provided authentic use of UAS it was constrained by logistics and unpredictability. Neither environment triggered systematic UAS risk assessment or explicit airspace coordination, revealing training gaps beyond simulation fidelity. Findings highlight the complementary strengths of both formats: VS excels in building foundational skills and ensuring scenario control, while LS fosters equipment familiarity and operational confidence in real-world conditions, providing actionable insights for designing effective UAS-integrated multi-agency exercises.